2022
DOI: 10.7554/elife.70763
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis reveals translationally relevant processes in mouse models of malaria

Abstract: Recent initiatives to improve translation of findings from animal models to human disease have focussed on reproducibility but quantifying the relevance of animal models remains a challenge. Here, we use comparative transcriptomics of blood to evaluate the systemic host response and its concordance between humans with different clinical manifestations of malaria and five commonly used mouse models. Plasmodium yoelii 17XL infection of mice most closely reproduces the profile of gene expression changes seen in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 101 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…2 ; Supplemental Table 6 ). To determine which of these differentially expressed orthologs have the biggest effect in fold-change between bacteriocytes and body for both species similar to Korb et al 19 and Georgiadou et al 20 we conducted PCA where axis 1 and 2 explained ~ 53.3% and 46.7% of the variance in the data, respectively. The top 100 shared orthologs (70 were non-redundant between both axis 1 and 2) with the highest positive and negative correlations with principal components 1 and 2 consist of 25 up-regulated and 45 down-regulated orthologs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ; Supplemental Table 6 ). To determine which of these differentially expressed orthologs have the biggest effect in fold-change between bacteriocytes and body for both species similar to Korb et al 19 and Georgiadou et al 20 we conducted PCA where axis 1 and 2 explained ~ 53.3% and 46.7% of the variance in the data, respectively. The top 100 shared orthologs (70 were non-redundant between both axis 1 and 2) with the highest positive and negative correlations with principal components 1 and 2 consist of 25 up-regulated and 45 down-regulated orthologs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To compare patterns of gene expression between species without species-specific variation, specifically focusing on genes associated with symbiosis that are differentially expressed in the bacteriocyte compared to body tissues, we conducted interspecies comparative transcriptomics analysis using PCA following the pipeline of Georgiadou et al 20 (see Supplemental Methods for detailed pipeline on interspecies transcriptomics analyses). Pcord (version 4.25) 52 was used for PCA analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This limitation (inherent to human field studies) could contribute to our observed differences in neutrophil and T cell proportions. Future work in animal models, where the infection and sampling times can be tightly controlled, could help to clarify the relationship between T cells and parasitemia, although important differences between animal models and human pathology exist ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Selection of inappropriate animal models is one possible cause of promising drugs failing at human trial stage [ 70 ]. Recently, comparative transcriptomic approaches have been used to identify translationally relevant mouse models for different human malarial phenotypes including CM, SMA, and hyperlactatemia [ 71 ], reasoning that the transcriptome may reflect many of the biological processes associated with disease. This approach could be used to identify animal models in which there is concordance of biological processes relevant to the specific therapeutic target and treatment between the mouse model and human disease, maximising the chance that results from the mouse model will be translatable to humans.…”
Section: Therapeuticsmentioning
confidence: 99%